The development and validation of the Meaning Making in Grief Scale. Issue 1 (2nd January 2022) - Yang, NaYeon; Lee, Sang Min
Abstract: The current study aimed to develop and investigate the psychometric properties of the Meaning Making in Grief Scale based on contemporary approaches to bereavement adaptation as a meaning reconstruction process. The research entailed three steps: scale development, exploratory factor analysis, and confirmatory factor analysis. The current 21-item scale was composed of three subscales: Meaning of the Significant Other, Being Present, and Coping and Growth. Support was found for the reliability and validity of the scale, as reflected in the high levels of coherence of the subscales and their hypothesized correlation with established measures of meaning and grief symptomatology.